2014
DOI: 10.3109/03630269.2014.892884
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation Status of β-Thalassemia Minor and Hb H Disease, and Its Association with Glycerol Lysis Time (GLT50)

Abstract: β-Thalassemia (β-thal), especially β-thalassemia major (β-TM), is reported to be related to reactive oxygen species (ROS) and enhanced oxidation status. It is reflected by increased malondialdehyde (MDA), by membrane lipid peroxidation and decreased by the newly developed total antioxidant capacity (TAC). However, there is less evidence for β-thal minor and Hb H (β4) disease on its association with oxidation status. On the other hand, hemolysis by glycerol lysis time (GLT50) is invariably prolonged in thalasse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“… 7 However, there are some reports about elevated oxidative stress in patients with th-minor associated with increased lipid peroxidation and decreased catalase activity. 20 , 21 But in th-minor the ferritin level is within normal limits and the anemia is usually not serious with Hb levels >9 mg/dL. 2 Eventually, the oxidative status is most likely less than th-major in th-minor.…”
Section: Discussionmentioning
confidence: 99%
“… 7 However, there are some reports about elevated oxidative stress in patients with th-minor associated with increased lipid peroxidation and decreased catalase activity. 20 , 21 But in th-minor the ferritin level is within normal limits and the anemia is usually not serious with Hb levels >9 mg/dL. 2 Eventually, the oxidative status is most likely less than th-major in th-minor.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been demonstrated that such patients experience decreased antioxidant capacity and increased products of peroxidative damage [4]. Enhanced oxidation status in β-TM is reflected by increased malondialdehyde (MDA), as a result of excess α-chains in erythrocytes and erythroblasts being unstable and prone to denaturation and oxidation, peroxidation of tissues that leak MDA into the blood, as well as depleted antioxidant capacity lowering defense to oxidants [5,6]. Liver lipid peroxidation also increases leakage of ferritin into the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Hb Hachioji was not separated on IEF. In addition, his instability (isopropanol) test was negative, while GLT 50 , which is prolonged by oxidative stress in thalassemia and unstable hemoglobinopathies, was prolonged [10]. At first, it was thought that Hb Hachioji presented as a highly unstable variant, which in erythrocytes prematurely denatured and precipitated, resulting in Heinz body formation with no Hb Hachioji remaining.…”
Section: Discussionmentioning
confidence: 99%
“…Blood was taken by venipuncture with EDTA as an anticoagulant. The blood was subjected to routine hematological analysis and measurement of half glycerol lysis time GLT 50 [9,10]. Hb F was quantitated by cation exchange HPLC for HbA 1c (HPLC 723 G8 V R ; Tosoh, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation